Study on Mechanical and Electrical Coupling characteristics of Milling system based on CMAC-PID Compound Control. (October 2019) - Tao, Lin; Zhao, Yue; Liu, Aoxiang; Zhao, Yuan; Zhao, Jinfang; Liu, Yefeng
Abstract: Taking boring and milling machining center as the research object, analyze and optimize the dynamic characteristics of milling control system. Use Simulink software to create mathematical model and simulate the dynamic characteristics of milling control system. Based on the theory of CMAC, consider the theory of the CMAC-PID compound control in the way of M function in Simulink Control language. Apply the theory, calculate the relevant parameters of milling system and model its transfer function, and all the parameters are solved by CMAC-PID compound control in Simulink. Verify the optimization of milling control system, and obtains the method of optimizing the mechanical and electrical coupling characteristics based on the CMAC-PID compound control theory.